New Insights Into the Role of Mitochondria Quality Control in Ischemic Heart Disease - Xin, Yanguo; Zhang, Xiaodong; Li, Jingye; Gao, Hui; Li, Jiayu; Li, Junli; Hu, Wenyu; Li, Hongwei (Frontiers in Cardiovascular Medicine, 2021)
IHD is a significant cause of mortality and morbidity worldwide. In acute phase, it’s demonstrated as myocardial infarction and ischemia-reperfusion injury, while in chronic stage, ischemic heart is mainly characterized by adverse myocardial remodelling. Although interventions such as thrombolysis and percutaneous coronary intervention could reduce the death risk of these patients, the underlying cellular and molecular mechanisms need more explorations. Mitochondria are crucial to maintain the physiological function of the heart. During IHD, mitochondrial dysfunction results in the pathogenesis of ischemia heart disease. Ischemia drives mitochondrial damage not only due to energy deprivation, but also to other aspects such as mitochondrial dynamics, mitochondria-related inflammation etc. Given the critical role of mitochondrial quality control in the pathological process of ischemia heart disease, in this review, we will summarize the efforts in targeting mitochondria (such as mitophagy, mtROS and mitochondria-related inflammation) on IHD. In addition, we will briefly revisit the emerging therapeutic targets in this field.